Clinical manifestations of influenza and performance of rapid influenza diagnostic test: A university hospital setting - Varistha Phetcharakupt (2022)
Background: Rapid influenza diagnostic test (RIDT) is a diagnostic tool that detects the influenza virus nucleoprotein antigen. The RIDT is widely used in clinical practice because it is simple and cost-effective, and provides results within 10-15 minutes. Objective: We aimed at evaluating the sensitivity and specificity of the Sofia® RIDT compared with the Luminex® multiplex polymerase chain reaction (PCR). The other goal was to determine the predicting factors for diagnosing influenza among individuals with influenza-like illness (ILI). Method: Patients with ILI who had the results of both tests were retrospectively reviewed. We determined the performances of the RIDT. Results: A total of 473 patients were included with a median age of 58 (interquartile range 41-74) years. Of these, 47.1% were male, and 16.2% were diagnosed with influenza by the RIDT or RT-PCR's positive test. For influenza A, the RIDT showed a sensitivity of 76.3% (95% confidence interval [CI] 59.8-88.6) and a specificity of 97.9% (95% CI 96.1-99.0), whereas for influenza B, it showed a sensitivity of 47.1% (95% CI 23.0-72.2) and a specificity of 97.1% (95% CI 95.2-98.5). Patients with influenza were more likely to present with fever (81.8% vs 63.1%), cough (81.8% vs 66.1%), and rhinorrhea (41.6% vs 26.5%) compared to those without influenza (P < 0.05, all), and had a higher proportion of pneumonia (19.5% vs 10.6%, P = 0.029) and acute respiratory distress syndrome (5.2% vs 1.5%, P = 0.063). The predicting factors for influenza among patients presented with ILI were cough (odds ratio [OR] 2.77; 95% CI 0.21-0.81, P = 0.010), rhinorrhea (OR 1.87; 95% CI 1.03-3.36, P = 0.037), and higher body temperature (OR 1.64; 95% CI 1.23-2.19, P = 0.001). Conclusions: The sensitivity of the RIDT for the diagnosis of influenza is fair in contrast to the specificity. Among patients with ILI, cough, rhinorrhea, and higher body temperature might be factors for predicting influenza.